SISTEM KEAMANAN RUMAH OTOMATIS MENGGUNAKAN SENSOR PIR, SENSOR SUHU, SENSOR GAS YANG TERHUBUNG DENGAN TELEPON SELULER BERBASIS MIKROKONTROLER ATMEGA8 DAN MIKROKONTROLER ATMEGA162 DENGAN BACKUP DAYA - Sekar A, Khanina Rizki; Subali, Subali (Gema Teknologi, 2013)
Khanina Rizki Sekar A, Subali, in paper Auto home security system using PIR sensor, temperature sensor, gas sensor connected with mobile phone based on microcontroller atmega162 and atmega8 with backup power explain that given the innumerable acts of criminality is happening around us, especially that threaten the security of residence so that the sense of security and peace becomes expensive. Along with the development of increasingly advanced technology make things easier including the automated home security systems are equipped with sensors, microcontrollers used as modem wavecom regulator as well as an information medium. Where in this system, every room in the house mounted sensor that functions to monitor the condition of the house. The sensor used is a PIR sensor for motion detection, temperature sensor to determine the room temperature and gas sensors to detect gas leaks. Results of the work detection sensor will be processed by a microcontroller ATmega8 then forwarded to the ATMega162 microcontroller via a serial port. Further information will be sent to the mobile phone via modem wavecom homeowners, so homeowners can know the condition of the house. The system is equipped with a battery backup, intended for home security control system to keep working in case of power outage suddenly. Keywords: PIR Sensor, Temperature Sensor, Gas Sensor, Microcontroller, Battery Backup